Table of contents, editorial board, introduction from the editor, and other front matter - Hal R. Taylor (Journal of Applied Communications, 1982)
Editorial front matter and table of contents for vol.65, no.2, Apr-June (1982) of TheACE Quarterly, Official Journal of the Agricultural Communicators in Education